The Influence of Merdeka Curriculum Learning and Teacher Work Motivation on Learning Quality in Public Elementary Schools - Triyanto Triyanto; Nurlina Nurlina; Alhadi Yan Putra (Journal of Social Work and Science Education, 2027)
Learning quality is a major indicator of elementary school effectiveness because it reflects the quality of planning, classroom implementation, learning interaction, assessment, and continuous instructional improvement. This study examines the influence of Merdeka Curriculum learning and teacher work motivation on learning quality in public elementary schools in Karang Agung Ilir District, Banyuasin Regency. The study used a quantitative ex post facto design. The respondents were 91 teachers selected from public elementary schools in the district. Data were collected through questionnaires measuring Merdeka Curriculum learning, teacher work motivation, and learning quality. The instruments were developed from relevant indicators and were tested before being used in the main study. The data were analyzed using descriptive statistics, assumption testing, simple linear regression, and multiple linear regression with SPSS version 26. The results show that Merdeka Curriculum learning had a positive and significant influence on learning quality, with t = 7.545, R = 0.625, and R² = 0.390. Teacher work motivation also had a positive and significant influence on learning quality, with t = 5.042, R = 0.471, and R² = 0.222. Simultaneously, Merdeka Curriculum learning and teacher work motivation influenced learning quality, with F = 32.910, R = 0.654, and R² = 0.428. These findings indicate that learning quality improves when curriculum implementation is supported by motivated teachers. The study contributes to educational management by showing that curriculum reform and teacher motivation should be developed together to strengthen learning quality in elementary schools.